Enhanced removal of Cu(II) by photocatalytic reduction using maghemite PVA-alginate separable beads: kinetic and equilibrium studies - Ee, Ting Wong (Taylor and Francis Inc., 2015)
The feasibility of Cu(II) removal by photoreduction using maghemite polyvinylalcohol-alginate beads was investigated. Photoreduction experiments were performed to investigate the influence of initial concentration and pH on the removal of copper(II) metallic ions. The fate of Cu(II) during the photoreduction process was investigated using the X-ray photoelectron spectroscopy. It was observed that the Cu(II) removal rate was faster under sunlight than without sunlight due to the reduction process of Cu(II) to Cu(I). The photoreduction results showed that the adsorption of Cu(II) ions followed a Langmuir Hinshelwood model with the photoreduction rate constant and adsorption coefficient values of 24.1 ppm/min and 0.0098 ppm-1, respectively.